1998
DOI: 10.1007/s005350050049
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal extrarenal angiomyolipoma with early gastric carcinoma

Abstract: We present a very rare case of a retroperitoneal extrarenal angiomyolipoma accompanied by early gastric cancer. A 41-year-old Japanese man, who had undergone surgery for a type IIc early gastric cancer 2 years earlier, was admitted to hospital presenting with back pain and abdominal fullness. Computed tomographic scanning and magnetic resonance imaging of the abdomen disclosed a massive fatty tumor extending from the hepatic hilus to the retroperitoneum. A large retroperitoneal tumor mass with no sign of invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…However, all of these cases were associated with renal angiomyolipoma and TS. This case was not associated with malignant tumor, but Tang et al reported an angiomyolipoma case of appendix carcinoid and Mogi et al reported a case of gastric cancer [4,11]. Although the number of cases of primary angiomyolipoma of the spleen is extremely small, it is necessary to consider the malignant complications.…”
Section: Discussionmentioning
confidence: 90%
“…However, all of these cases were associated with renal angiomyolipoma and TS. This case was not associated with malignant tumor, but Tang et al reported an angiomyolipoma case of appendix carcinoid and Mogi et al reported a case of gastric cancer [4,11]. Although the number of cases of primary angiomyolipoma of the spleen is extremely small, it is necessary to consider the malignant complications.…”
Section: Discussionmentioning
confidence: 90%
“…Angiomyolipomas (AMLs) are rare complex mesenchymal neoplasms typically arising within the kidney and are composed of mature adipose tissue, smooth muscle cells, and thick-walled blood vessels [22]. Renal AMLs account for 1% of renal lesions, occurring more commonly in women [2] with an overall incidence in the general population of 0.07–0.3% [25].…”
Section: Discussionmentioning
confidence: 99%
“…Mogi et al [ 13 ] in 1998 reported a 41-year-old woman who 2 years earlier undergone surgery for type IIc early gastric cancer and who presented with back pain and fullness of her abdomen. She had CT scan and MRI scan of her abdomen and pelvis which revealed a massive fat tumour mass that had extended from the hepatic hilus to the retroperitoneum (in her right perinephric space as well as her perihepatic space).…”
Section: Literature Reviewmentioning
confidence: 99%